America the beautiful and violent: black youth & neighborhood trauma in Chicago - Voisin, Dexter R. (Columbia University Press, 2019)
The beginning -- The tale of two Americas -- Not all violence is the same : race- and place-based violence -- The road to concentrated poverty and neighborhood violence -- The scars of violence -- When violence and sex are entangled -- Living and parenting in the presence of everyday dangers -- Joining the broken pieces : practice and policy solutions and systems integrations -- Making a difference : rebuilding the village -- Notes -- Index.